THE EFFECT OF WAGES, INCENTIVES, AND SOCIAL SECURITY ON EMPLOYEE PERFORMANCE IMPROVEMENT IN MULTIFINANCE COMPANIES IN CENTRAL JAVA - Pemilia Sulistyowati; Edwin Zusrony; Sherly Dwi Ditzi Savitri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study was made to see the effect of wage variables, incentive variables, and social security variables on the performance of employees of multifinance company XY in the city of Salatiga. The number of respondents who were used as research samples as many as 30 people with saturated sampling technique, ie all the population was used as respondents. Collecting data using a questionnaire by providing several questions related to the variables of wages, incentives, social security and employee performance. Measurement of research instruments using a Likert scale and data analysis using multiple linear regression. With the help of the SPSS 23 program, it is known that wages, incentives, and social security variables have a positive and significant influence on the performance variables of multifinance company XY employees in the city of Salatiga, this is evidenced by a significance value of less than 0.05. And simultaneously it is known from the F test, that the variables of wages, incentives, and social security have a significant influence of 0.000 on the employee performance variable.